Towards Better Delivery of Cannabidiol (CBD) - Sophie Anne Millar; Ryan Francis Maguire; Andrew Stephen Yates; Saoirse Elizabeth O'Sullivan (MDPI AG, 2020)
Cannabidiol (CBD) has substantial therapeutic potential, but its development as an effective drug by the pharmaceutical industry is hindered by intrinsic characteristics such as low bioavailability, low water solubility, and variable pharmacokinetic profiles. Importantly, lack of patentability of the drug substance also limits the likelihood of an expensive, full development programme in anything other than orphan indications. Potential avenues to overcome these issues with CBD include self-emulsifying drug delivery systems, improved crystal formulations and other solid-state delivery formulations, which are mostly in the pre-clinical or early clinical stages of development. This review identifies issues compromising current delivery of solid-state CBD, and how advanced pharmaceutical development strategies can enable CBD to realise the full potential as a successful therapeutic agent.